"A Throne Will Be Established in Steadfast Love": Welcoming Refugees and the Davidic Kingdom in Isaiah 16:1–5 - Aspray, Barnabas ca. 20./21. Jh. (Open theology, 2021)
All commentators agree that Isaiah 16:1-5 is about refugees, yet the passage’s implications for forced migration have not yet been investigated. This article argues that it contains a prophetic call by Isaiah, speaking with God’s authority, that Jerusalem should welcome the Moabite refugees who have fled there for safety. Isaiah tells Jerusalem that by welcoming these refugees they are participating in the coming of a Kingdom and a Davidic King who will rule with justice, righteousness, love, and faithfulness.